Integrating the pastoral component in agricultural systems - Carvalho, Paulo Cesar de Faccio (2018)
This paper aims to discuss the impact of the introduction of pastures and grazing animals in agricultural systems. For the purposes of this manuscript, we focus on within-farm integrated crop-livestock systems (ICLS), typical of Southern Brazil. These ICLS are designed to create and enhance the synergisms and emergent properties have arisen from agricultural areas where livestock activities are integrated with crops. We show that the introduction of the crop component will affect less the preceding condition than the introduction of the livestock component. While the introduction of crops in pastoral systems represents increasing diversity of the plant component, the introduction of animals would represent the entry of new flows and interactions within the system. Thus, given the new complexity levels achieved from the introduction of grazing, the probability of arising emergent properties is theoretically much higher. However, grazing management is vital in determining the success or failure of such initiative. The grazing intensity practiced during the pasture phase would affect the canopy structure and the forage availability to animals. In adequate and moderate grazing intensities, it is possible to affirm that livestock combined with crops (ICLS) has a potential positive impact. As important as the improvements that grazing animals can generate to the soil-plant components, the economic resilience remarkably increases when pasture rotations are introduced compared with purely agriculture systems, particularly in climate-risk situations. Thus, the integration of the pastoral component can enhance the sustainable intensification of food production, but it modifies simple, pure agricultural systems into more complex and knowledge-demanding production systems.